(untitled) (Nigerian Journal of Technology, 2005)
Field studies were conducted at the National Centre for Agricultural Mechanization (NCAM), Ilorin on a sandy loam soil to evaluate the effect of the imposition of different levels of tractor forward speed during tillage on some soil physical properties. The forward speed was varied from 1.0 to 10.6km/h: The depth of tillage was maintained constant at 20cm throughout the operations. The soil physical parameters measured were cone penetration resistance (cone index CI), shear strength (SS), bulk density (BD), moisture content (MC), and clod mean weight diameter (MWD). Results indicate significant differences in soil physical conditions arising from different levels of tractor forward speed. A forward speed of approximately 7km/h resulted in appreciable amelioration of soil structure as reflected in improvements in the soil strength properties and maximum reduction in clod mean weight diameter. Soil strength properties generally decreased with increasing speed but increased with depth of tillage. A predictive model depicting the most vital soil physical parameters affected by tractor speed was developed